In situ hydrogenation of model compounds and raw bio-oil over Raney Ni catalyst. (1st January 2015) - Xu, Ying; Long, Jinxing; Liu, Qiying; Li, Yanbin; Wang, Chenguang; Zhang, Qi; Lv, Wei; Zhang, Xinghua; Qiu, Songbai; Wang, Tiejun; Ma, Longlong
Abstract : Graphical abstract: Over Raney Ni catalyst, the aqueous phase reforming (APR) of methanol could couple with the hydrogenation of the model compounds of bio-oil and the raw bio-oil. The hydrogen product from the APR of methanol could offer hydrogen source for the upgrading of the raw bio-oil. The main products of acetone and phenol were isopropanol and cyclohexanol. At 220 °C and 3 MPa, the conversion of acetone and phenol reached the highest point with 55.76% and 64.65% and the bio-oil was improved not only on the appearance but also on the composition significantly. The contents of ketone/aldehyde and organic acids decreased from 30.36% and 39.89% to 9.32% and 30.25% respectively. The contents of alcohols and esters increased from 8.89% and 4.9% to 16.33% and 20.53%. During the in situ hydrogenation process, hydrogenation and esterification were the main reactions in the bio-oil. Highlights: We proposed a novel hydrogenation method in mild condition without adding external hydrogen. The methanol APR and hydrogenation of model compounds and the raw bio-oil could couple with each other. The hydrogen generated in situ by the APR of methanol could be used for the hydrogenation of the raw bio oil. After in situ hydrogenation, the appearance and composition of the bio oil was improved significantly. Abstract: The conversion of renewable energy is one of the most important research fields. A novel upgrading method of bio-oil produced from fast pyrolysis of biomass was reported in the paper. Methanol, as hydrogenation liquid donor, was used in the hydrogenation process instead of hydrogen gas. The effects on the aqueous phase reforming (APR) of methanol and the in situ hydrogenation of model compounds (acetone and phenol) and bio-oil were investigated. The results showed that over Raney Ni catalyst, the in situ hydrogenation could couple with the APR of methanol. The conversions of acetone and phenol reached the highest point with 55.76% and 64.65% respectively at 220 °C, 3 MPa(N2 ). The results of GC–MS analysis showed that after upgrading, the content of ketones & aldehydes and organic acids decreased from 30.36% and 39.89% to 9.32% and 30.25% respectively. The content of alcohols and esters increased from 8.89% and 4.9% to 16.33% and 20.53%. During the upgrading of bio-oil, hydrogenation and esterification were the main reactions.